Morphology and phylogeny of Pseudocercospora trifoliorum sp. nov. (Mycosphaerellaceae) on Grona triflora from India - Rajwar, Soumyadeep; Singh, Raghvendra; Kumar, Shambhu; Singh, Paras Nath; Singh, Alok Kumar (Phytotaxa, 2025)
Pseudocercospora trifoliorum, a newly discovered foliicolous hyphomycetous fungus on Grona triflora (Fabaceae), is taxonomically described and illustrated. Its phylogeny was determined using LSU, RPB2, and ITS regions to analyze evolutionary relationships. The taxon is compared to closely related Pseudocercospora species through morphological traits and molecular analysis, improving insights into its classification and evolutionary relationships.